European Union - The Second Founding The Changing Rationale of European Integration - Kühnhardt, Ludger (Schriften des Zentrum für Europäische Integrationsforschung (ZEI), 2008)
Prof. Dr. Ludger Kühnhardt, Director at the renowned Center for European Integration Studies (ZEI) at the University of Bonn is presenting a broadly structured study about the first fifty years of European integration, its geopolitical context and academic reflection. His study is based on the two-fold thesis that since a few years, the European Union is going through a process of its Second Founding while simultaneously changing its rationale. The original founding of European integration in 1957 was based on the notion of internal reconciliation among European states and societies. Since the 1990""s European integration has become, increasingly, a political project with implications for the internal structure of its member states and their societies. At the same time, with the end of the Cold War, the rational of European integration has begun to change: European integration is about a new global role of Europe, its contribution to the management of global affairs and its ability to cope with the effects of globalization on Europe. Inside the EU, the Second Founding is about a new contract between political elites and the people of Europe in order to solidify legitimacy and effectiveness for this unique experiment in European history. Prof. Dr. Ludger Kühnhardt has been Director at the Center for European Integration Studies (ZEI) since 1997. He is author of thirty books and edits the volumes of ZEI at Nomos.